P472 The mechanism of action of antifungal activity of Zanthoxylum armatum fruit's oil against Candida cells does not involve ROS generation. (20th September 2022) - Pasrija, Ritu
Abstract: Poster session 1, September 21, 2022, 12:30 PM - 1:30 PM: Objective: To explore the antifungal activity of Zanthoxylum armatum fruit's oil against different Candida species and its mechanism of action. Methods: The Z. armatum fruit's oil activity was assessed against C. albicans, C. krusei, C. glabrata, C. parapsilosis, C. tropicalis, and C. guilliermondii through different drug susceptibility assays including, MIC, agar diffusion and spot assay. The mechanism of action was explored through sterol analysis, germ tube inhibition, epithelial cells adherence, and ROS generation. Results: The oil from the fruits of Z. armatum was subjected to GC-MS analysis, and linalool (72%) was found as the major component. The drug susceptibility measured through different methods, including minimum inhibitory concentration (MIC), where end-point was 3% v/v for different species tested, and the same pattern was observed in agar diffusion and spot assay. The antifungal activity was found to be fungicidal in nature and the major reason appeared to be the reduction in ergosterol levels inside cells. It resulted in lowered germ tube formation, an important indicator in virulence of C. albicans . The oil reduced adherence of Candida cells to buccal epithelium significantly, which is the first step in invasion, biofilm formation, and damage to oral epithelial cells. Interestingly, unlike most antifungals, where reactive oxygen species generation mediated killing is involved, was not found significant in the present study. Conclusions: The Z. armatum fruits oil exerts its antifungal activity by inhibiting ergosterol formation and reduced germ tube formation.